Technical Efficiency Analysis of Rice Farming in Ardimulyo Village, Singosari District, Malang Regency - Zahroh, Devi Senia; Sujarwo; Deny Meitasari (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
Ardimulyo Village is one of the rice center villages in the Singosari Sub-district. Rice Productivity in Ardimulyo Village is 6.8 tons/ha, but according to BPP Singosari, the optimal productivity reaches 8 tons/ha so there is an opportunity to increase it. The low productivity is thought to be due to inefficient use of production inputs. The purpose of this research were : (1) to analyze the production factors that significantly affect rice production, (2) to analyze the level of technical efficiency of rice farming, (3) to analyze the socioeconomic factors that affect the technical efficiency of rice farming. The analysis method used in this research is the SFA (Stochastic Frontier Analysis) and the tobit regression analysis to answer the third objective. The results of the analysis obtained in this study indicate that (1) Production factors that significantly and positively affect rice production are land area, the amount of phonska fertilizer and the amount of pesticides, (2) The average value of the technical efficiency level of rice farmers in Ardimulyo Village is 0.738, (3) Socio-economic factors that have a significant and positive effect on the technical efficiency of rice farming are the length of farming experience and the frequency of participation in extension, while land ownership status has a negative effect. The suggestion that can be made is that farmers can combine the use of significant inputs including land area, phonska fertilizers and pesticides in accordance with the recommendations of BPP Singosari so that the farming carried out can achieve technical efficiency.